Career development, work environment and challenges of hotel middle managers / Mohd Onn Rashdi Abd Patah and Mohd Salehuddin Mohd Zahari - Abd Patah, Mohd Onn Rashdi; Mohd Zahari, Mohd Salehuddin (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Advancing in the hotel industry for employees depends on their willingness to face and overcome several challenges in mostly a difficult work environment. The aim of this paper is to explore and report the career development, work environment and challenges of hotel middle managers in Malaysia. This study uses qualitative research approach and data collection was done through semi-structured interviews and narrative analysis. A total of 14 hotel head of department (middle managers) from hotels in Kuala Lumpur, Malaysia were interviewed. Participants were initially approached through their respective Human Resources Managers and through alternative platform such as LinkedIn, a professional social media platform. They were selected based on their tenure as middle managers (five years or more on the post). Atlas.ti™ software was used to transcribe the recorded interviews. The results highlighted new perspective on the participants' career construction and pathways which was actually self-constructed based on the opportunities that they had, changes in their life phases as a hoteliers and other factors such as their family support. This study contributes by bringing on the importance of seeking new managerial knowledge, continuously attending trainings for skill enhancements, variety of work experiences, and pursuing new opportunities.